Cyber-physical system for control the heat and mass transfer in the oil reservoir and producing pumping well - Konyukhov, Ivan; Konyukhov, Vladimir (Cybernetics and physics, 2019)
A special cyber-physical system is developed to control transient heat and mass transfer during the commissioning of the unified oil production complex consisted of oil reservoir, producing well equipped with electric submersible centrifugal pump, well production tree and ground-based control station. Two main elements of cyber-physical system are following: – computer simulator of heat and mass transfer in virtual oil production complex based on mathematical and numerical models of such processes along with simultaneous visualization of computational results; – portable imitation hardware of real ground-based equipment which is realized as 3D-printed plastic model consisted of control elements (pipeline valves, drossel chamber, ground-based control station) and recording devices (manometers, level indicator, liquid sampler and control station itself). Mechanisms of these elements are replaced by Arduino microchips to simulate the operation of real devices. An important feature of the cyber-physical system is the data exchange and interaction between oil production computer simulator and microcontroller software. Data transfer is going through the COM-ports of computer and microcontroller. The simulator sends calculated working characteristics of oil production complex to the memory of microcontroller, which not only analyzes incoming data but also displays it on the recording devices and forms necessary control parameters, which are sent back to simulator and affect the further behavior of the whole complex. Different elements of the CPS provides the possibility to control and visualize the commissioning of the oil production complex under consideration and the whole system is oriented to simulate the real technological actions performing by specialists in oil production.